2020
DOI: 10.3390/su12031040
|View full text |Cite
|
Sign up to set email alerts
|

Nurse Practitioners’ Work Values and Their Conflict Management Approaches in a Stressful Workplace: A Taiwan Study

Abstract: Globalization has created an urgent need to understand management practices in different cultures. This study examines Confucianism-based work values of nurse practitioners in Taiwan and explores their impact on conflict management approaches in order to help health practitioners maintain sustainable work relationships and improve organizational effectiveness in an increasingly stressful workplace. Based on the data from 259 nurse practitioners in Taiwan, this study shows that nurse practitioners in Taiwan con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…• Values for working conditions 46,63,77,79 • Values for salary 5,10,21,22,25,35,46,47,63,77,79,81 • Values for benefits 63,81 • Values for job security 4,14,21,25,47,79,80 • Values for financial stability 48 • Values for occupational stability 10,32,81 • Values for comfort 4,10,80 • Values for the working environment 10…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…• Values for working conditions 46,63,77,79 • Values for salary 5,10,21,22,25,35,46,47,63,77,79,81 • Values for benefits 63,81 • Values for job security 4,14,21,25,47,79,80 • Values for financial stability 48 • Values for occupational stability 10,32,81 • Values for comfort 4,10,80 • Values for the working environment 10…”
Section: Discussionmentioning
confidence: 99%
“…The term "values" 18 is defined in the Cambridge dictionary as "the Seibert et al 21 Work values are defined as an individual's concepts or beliefs about desirable end states (e.g., high pay) or types of behavior (e.g., working with people) and are a specific expression of basic values in the work setting. 19 Jing et al 22 Work values refer to work-related norms individuals comply with in performing jobs, working with colleagues, and interacting with other stakeholders in the workplace. 23,24 Work values reveal an individual's evaluative tendency toward work and reflect his/her attitudes toward all job-related rewards, level of participation and engagement, and career ambition.…”
Section: Uses Of the Conceptmentioning
confidence: 99%
See 2 more Smart Citations
“…There is a solid conviction that people essentially vary in their tendency and use of contention in taking care of conflict management styles. It has been demonstrated that males will in general have a specific inclination toward contending systems which are dominating strategy while female workers are bound to utilize non-contending methodologies (avoiding, integrating, and compromising) (Jing, Ma, Ma, Chen, & Cheng, 2020)…”
Section: Introductionmentioning
confidence: 99%